Curbing global warming with phase change materials for energy storage - Anisur, M.R.; Mahfuz, M.H.; Kibria, M.A.; Saidur, Rahman; Metselaar, I.H.S.C.; Mahlia, T.M.I. (Elsevier, 2013)
The application of thermal energy storage (TES) system with phase change material (PCM) is an effective way for energy conservation and greenhouse gas (GHG) emission reduction. Global warming is increasing along with the energy consumption. Many researchers are concerned about this present global environmental problem for fossil-fuel burning. Thermal energy storage system with phase change material is observed as a potential candidate for mitigating this problem. This paper emphasizes the opportunities for energy savings and greenhouse-gas emissions reduction with the implementation of PCM in TES systems. For instance, about 3.43 of CO 2 emission by 2020 could be reduced through the application of PCM in building and solar thermal power systems. Similarly, energy conservation and GHGs emission reduction by other PCM applications for thermal comfort of vehicles, transport refrigeration, engine cold start, greenhouse and waste heat management are also presented. In addition, some present investigations on the performance improvement of the phase change materials are addressed.